THE INFLUENCE OF SERVICE QUALITY ON PATIENT SATISFACTION AT THE FAIRY CLINIC - Danang Djoko Susilo; Donny Christopher; Nita Mustika; Yan Ari Nugroho; Suwandono Suwandono (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze the effect of service quality on patient satisfaction at Fairy Clinic. Service quality is one of the main factors determining patient satisfaction with healthcare services. This study employed a quantitative approach with a survey method. The study population was all patients treated at Fairy Clinic during April–June 2026. A sample of 150 respondents was selected using accidental sampling. Data were collected through a questionnaire using a Likert scale measuring five dimensions of service quality (tangible, reliability, responsiveness, assurance, and empathy) and patient satisfaction. Data analysis was performed using validity and reliability tests, simple linear regression analysis, t-tests, and the coefficient of determination (R²). The results showed that service quality had a positive and significant effect on patient satisfaction, with a regression coefficient of 0.781, a calculated t-value of 15.842, greater than the t-table of 1.976, and a significance value of 0.000 (<0.05). The coefficient of determination of 62.8% indicates that service quality explains 62.8% of the variation in patient satisfaction, with the remainder influenced by factors outside the study. This finding suggests that the better the service quality provided by Fairy Clinic, the higher the patient satisfaction level.